The methylome of the gut microbiome: disparate Dam methylation patterns in intestinal Bacteroides dorei - Leonard, Michael T.; Davis-Richardson, Austin G.; Ardissone, Alexandria N.; Kemppainen, Kaisa M.; Drew, Jennifer C.; Ilonen, Jorma; Knip, Mikael; Simell, Olli; Toppari, Jorma; Veijola, Riitta; Hyöty, Heikki; Triplett, Eric W. (Frontiers in Microbiology, 2014)
Despite the large interest in the human microbiome in recent years, there are no reports of bacterial DNA methylation in the microbiome. Here metagenomic sequencing using the Pacific Biosciences platform allowed for rapid identification of bacterial GATC methylation status of a bacterial species in human stool samples. For this work, two stool samples were chosen that were dominated by a single species, Bacteroides dorei. Based on 16S rRNA analysis, this species represented over 45% of the bacteria present in these two samples. The B. dorei genome sequence from these samples was determined and the GATC methylation sites mapped. The Bacteroides dorei genome from one subject lacked any GATC methylation and lacked the DNA adenine methyltransferase genes. In contrast, B. dorei from another subject contained 20,551 methylated GATC sites. Of the 4,970 open reading frames identified in the GATC methylated B. dorei genome, 3,184 genes were methylated as well as 1,735 GATC methylations in intergenic regions. These results suggest that DNA methylation patterns are important to consider in multi-omic analyses of microbiome samples seeking to discover the diversity of bacterial functions and may differ between disease states.